2021
DOI: 10.1021/acsomega.1c04893
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Iron Migration Mechanism for the Cretaceous Sediment Color Variations in Sichuan Basin, China

Abstract: Cretaceous continental sediments in Sichuan Basin, China, have different colors, and the reasons for their formation are not determined. Based on mineralogical and geochemical characteristics, red beds and nonred beds in the Upper and Lower Cretaceous sedimentary strata in the western Sichuan Basin are described and tested in this study. The test and analysis of the mineral composition, element content, and iron speciation of mudstone samples with gray-green, gray, and red colors in Cangxi, Bailong, and Guanko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 85 publications
(180 reference statements)
0
1
0
Order By: Relevance
“…For example, the content of Fe2O3 or hematite in the red beds is higher than that in the grey beds (Hu et al 2006). The chemical compositions of red beds (1536 groups data) with different geological ages and various lithologies such as conglomerate, sandy conglomerate, sandstone, siltstone, shale and mudstone were collected from the previous studies as shown in Supplementary Table 2 (e.g., (Gao et al 2017;Hong et al 2009;Jiang et al 2022;Kong et al 2018;Liu et al 2007;Liu et al 2020;Liu et al 2006;Uchida et al 2000;Wild et al 2017;Xue et al 2023;Yang et al 2016;Zhang et al 2008;Zhao et al 2005;Zhu et al 2003) May, 2023, using the following parameters: material = sedimentary and rock name = breccia. ), claystone (Supplementary Table 12 -3,790 groups data.…”
Section: Data Collectionmentioning
confidence: 99%
“…For example, the content of Fe2O3 or hematite in the red beds is higher than that in the grey beds (Hu et al 2006). The chemical compositions of red beds (1536 groups data) with different geological ages and various lithologies such as conglomerate, sandy conglomerate, sandstone, siltstone, shale and mudstone were collected from the previous studies as shown in Supplementary Table 2 (e.g., (Gao et al 2017;Hong et al 2009;Jiang et al 2022;Kong et al 2018;Liu et al 2007;Liu et al 2020;Liu et al 2006;Uchida et al 2000;Wild et al 2017;Xue et al 2023;Yang et al 2016;Zhang et al 2008;Zhao et al 2005;Zhu et al 2003) May, 2023, using the following parameters: material = sedimentary and rock name = breccia. ), claystone (Supplementary Table 12 -3,790 groups data.…”
Section: Data Collectionmentioning
confidence: 99%